Calidad del servicio y su incidencia en la captación de clientes de la Cooperativa de Ahorro y Crédito Riobamba Limitada, sucursal Guano. - Guapulema Narvaez, Elisa Abigail (2023)
The objective of this investigation was to determine the quality of service and its impact on customer acquisition of the Cooperativa de Ahorro y Crédito Riobamba Limitada Sucursal de Guano, using a descriptive and correlational quantitative methodology, data were collected through surveys of 13 staff members working in the institution and 255 partners, to study the quality of service the SERVQUAL questionnaire was applied in Likert scale and binary scale Yes and No. In addition, data processing was performed, and the reliability of the surveys using Crbach's alpha and hypothesis testing using the Chi-square test using Excel and SPC applications. In addition, the data were processed, the reliability of the surveys was tested using Cronbach's alpha and the hypotheses were tested using the Chi-square test using Excel and SPSS applications, which helped to determine the quality of service that affects customer acquisition. The results showed that the typical profile of the member has an age range between 28 and 37 years, high school education, and professional driver occupation, the key factors that the Cooperative most frequently implements to attract customers are offering quality service, door-to-door promotion, and advertising through social networks, these strategies have allowed it to attract new customers and maintain current ones. In this way, the proposal put forward proposes a model to improve the quality of service and help to attract customers.